Step * 1 1 1 1 1 of Lemma es-interface-accum-programmable


1. Info Type
2. es EO+(Info)@i'
3. Type
4. Type
5. EClass(A)
6. B
7. B ─→ A ─→ B
8. EClass(B)@i'
9. λB,r. if (#(B 0) =z 1)
        then if (#(r) =z 1) then {f[only(r);only(B 0)]} else {f[x;only(B 0)]} fi 
        else {}
        fi i.X,(self)'|
Y
∈ EClass(B)@i'
10. E@i
11. if (#(X es e) =z 1)
then if (#(Prior(λB,r. if (#(B 0) =z 1)
                      then if (#(r) =z 1) then {f[only(r);only(B 0)]} else {f[x;only(B 0)]} fi 
                      else {}
                      fi i.X,(self)'|) 
           es 
           e) =z 1)
     then {f[only(Prior(λB,r. if (#(B 0) =z 1)
                             then if (#(r) =z 1) then {f[only(r);only(B 0)]} else {f[x;only(B 0)]} fi 
                             else {}
                             fi i.X,(self)'|) 
                  es 
                  e);only(X es e)]}
     else {f[x;only(X es e)]}
     fi 
else {}
fi 
(Y es e)
∈ bag(B)
⊢ (Y es e)
if (#(X es e) =z 1)
  then if (#(Prior(Y) es e) =z 1) then {f[only(Prior(Y) es e);only(X es e)]} else {f[x;only(X es e)]} fi 
  else {}
  fi 
∈ bag(B)
BY
(Symmetry THEN NthHypEq (-1) THEN EqCD THEN Try (WithRuleCount 1000 Auto)) }

1
.....subterm..... T:t
2:n
1. Info Type
2. es EO+(Info)@i'
3. Type
4. Type
5. EClass(A)
6. B
7. B ─→ A ─→ B
8. EClass(B)@i'
9. λB,r. if (#(B 0) =z 1)
        then if (#(r) =z 1) then {f[only(r);only(B 0)]} else {f[x;only(B 0)]} fi 
        else {}
        fi i.X,(self)'|
Y
∈ EClass(B)@i'
10. E@i
11. if (#(X es e) =z 1)
then if (#(Prior(λB,r. if (#(B 0) =z 1)
                      then if (#(r) =z 1) then {f[only(r);only(B 0)]} else {f[x;only(B 0)]} fi 
                      else {}
                      fi i.X,(self)'|) 
           es 
           e) =z 1)
     then {f[only(Prior(λB,r. if (#(B 0) =z 1)
                             then if (#(r) =z 1) then {f[only(r);only(B 0)]} else {f[x;only(B 0)]} fi 
                             else {}
                             fi i.X,(self)'|) 
                  es 
                  e);only(X es e)]}
     else {f[x;only(X es e)]}
     fi 
else {}
fi 
(Y es e)
∈ bag(B)
⊢ if (#(X es e) =z 1)
then if (#(Prior(Y) es e) =z 1) then {f[only(Prior(Y) es e);only(X es e)]} else {f[x;only(X es e)]} fi 
else {}
fi 
if (#(X es e) =z 1)
  then if (#(Prior(λB,r. if (#(B 0) =z 1)
                        then if (#(r) =z 1) then {f[only(r);only(B 0)]} else {f[x;only(B 0)]} fi 
                        else {}
                        fi i.X,(self)'|) 
             es 
             e) =z 1)
       then {f[only(Prior(λB,r. if (#(B 0) =z 1)
                               then if (#(r) =z 1) then {f[only(r);only(B 0)]} else {f[x;only(B 0)]} fi 
                               else {}
                               fi i.X,(self)'|) 
                    es 
                    e);only(X es e)]}
       else {f[x;only(X es e)]}
       fi 
  else {}
  fi 
∈ bag(B)


Latex:



Latex:

1.  Info  :  Type
2.  es  :  EO+(Info)@i'
3.  A  :  Type
4.  B  :  Type
5.  X  :  EClass(A)
6.  x  :  B
7.  f  :  B  {}\mrightarrow{}  A  {}\mrightarrow{}  B
8.  Y  :  EClass(B)@i'
9.  \mlambda{}B,r.  if  (\#(B  0)  =\msubz{}  1)
                then  if  (\#(r)  =\msubz{}  1)  then  \{f[only(r);only(B  0)]\}  else  \{f[x;only(B  0)]\}  fi 
                else  \{\}
                fi  |\mlambda{}i.X,(self)'|
=  Y@i'
10.  e  :  E@i
11.  if  (\#(X  es  e)  =\msubz{}  1)
then  if  (\#(Prior(\mlambda{}B,r.  if  (\#(B  0)  =\msubz{}  1)
                                            then  if  (\#(r)  =\msubz{}  1)  then  \{f[only(r);only(B  0)]\}  else  \{f[x;only(B  0)]\}  fi 
                                            else  \{\}
                                            fi  |\mlambda{}i.X,(self)'|) 
                      es 
                      e)  =\msubz{}  1)
          then  \{f[only(Prior(\mlambda{}B,r.  if  (\#(B  0)  =\msubz{}  1)
                                                          then  if  (\#(r)  =\msubz{}  1)
                                                                    then  \{f[only(r);only(B  0)]\}
                                                                    else  \{f[x;only(B  0)]\}
                                                                    fi 
                                                          else  \{\}
                                                          fi  |\mlambda{}i.X,(self)'|) 
                                    es 
                                    e);only(X  es  e)]\}
          else  \{f[x;only(X  es  e)]\}
          fi 
else  \{\}
fi 
=  (Y  es  e)
\mvdash{}  (Y  es  e)
=  if  (\#(X  es  e)  =\msubz{}  1)
    then  if  (\#(Prior(Y)  es  e)  =\msubz{}  1)
              then  \{f[only(Prior(Y)  es  e);only(X  es  e)]\}
              else  \{f[x;only(X  es  e)]\}
              fi 
    else  \{\}
    fi 


By


Latex:
(Symmetry  THEN  NthHypEq  (-1)  THEN  EqCD  THEN  Try  (WithRuleCount  1000  Auto))




Home Index